APPLYING WORD CHAIN GAME TO IMPROVE STUDENTS’ VOCABULARY MASTERY - M. Fadhly Farhy Abbas (ELT-Lectura, 2014)
This Classroom Action Research (CAR) aimed to improve the students’ vocabulary mastery by applying theword chain game as a teaching technique. The students of SMPN 20 Pekanbaru particularly at grade VIII.6 were the participants of the research. There were 39 students who were taught by using word chain game to improve their vocabulary mastery. The Findings shows there was improvement of the students’ vocabulary mastery using the word chain game, it can be seen from the students’ score and the learning atmosphere. The data reveals, the students score was 81.2. The data also showing interesting, active, and joyful in the learning process. Based on the research findings, it can be concluded that the word chain game can help the students of SMPN 20 Pekanbaru at grade VIII.6 to improve their vocabulary mastery. This research finding implies that the use of the word chain game can be used in learning English particularly in teaching andlearning vocabulary.